Protective effect of Lactobacillus plantarum against Salmonella typhimurium in mice. - Shahlaa M. Salih; Zahraa K. Zedan (مجلة كلية الطب, 2011)
Background: Probiotics are defined as living microbial food supplements that beneficially affect the host by improving its intestinal balance. In recent years there is a great interest for viable microorganisms that promote or support a beneficial balance of microbial population of gastrointestinal tract. Probiotics may be consumed in different forms, comprising foods, mainly in fermented state and pharmaceutical products, mainly as capsules or in microencapsulated forms. Methods: Twelve albino mice were divided into four groups designated as 1, 2, 3 and 4. Each group consists of 3 mice, and subject to the followings treatments: Group 1: This group was used as a control. Group 2: This group was dosed with 0.1ml. of 0.5 × 105 cfu/ml of Lactobacillus plantarum culture. Group 3: This group was dosed with 0.1ml. of 0.5 × 105 cfu/ml Salmonella typhimurium culture. Group 4: this group was dosed with 0.1ml of 109cfu/ml Lactobacillus plantarum culture, and infected with 0.1ml of 0.5 × 105cfu/ml culture of Salmonella typhimurium, then histological sections were made from intestine and examined to evaluate protective effect of Lactobacillus plantarum. Results: Histopathological study exhibited that intestinal sections of mice infected with Salmonella typhimurium showed a necrosis, degenerative changes and inflammatory cells infiltration as compared with normal sections taken from uninfected mice, while treating with Lactobacillus plantarum prevented the histopathological effect of Salmonella typhimurium on mice intestine. Conclusion: Probiotic L. plantarum had a protective effect on intestine sections of mice infected with Salmonella typhimurium